Passive mode-locking performance of mixed Nd:La0.11Y0.89VO4 crystal - Xu, Honghao (2014)
Passive mode locking of a diode pumped Nd:La0.11Y0.89VO4 mixed crystal laser with a semiconductor saturable absorber mirror (SESAM) was experimentally investigated for the first time to our knowledge. Stable CW mode-locking has been achieved on both a-cut and c-cut mixed crystals. In case of the a-cut crystal, when a 2% output coupler (OC) was used, the shortest pulse obtained was 4.5 ps and the highest output power was 0.94 W, while when a 6% OC was used, the shortest pulse obtained was 6.8 ps and the highest output power was 5.16 W. In the latter case the optical conversion efficiency is 38% and the slope efficiency is 40.3%, respectively; with the c-cut crystal the shortest pulse achieved was 5.5 ps. Moreover, simultaneous mode locking at two close wavelengths of 1064.3 nm and 1066.2 nm was observed on the c-cut crystal. The mode locked pulse beating generated temporal interference fringe of 0.5 THz repetition rate.